Routine use of SARS-CoV-2 IgM and IgG Antibodies: A Practical Approach in Gabon - Iroungou, Berthe Amélie; Ossima, Arnaud Nze; Dikoumba, Annicet Clotaire; Bouassa, Aurore Prislya Bouassa; Mangouka, Guignali Laurette (Archives of Clinical and Biomedical Research, 2024)
Background: In late 2019, a novel coronavirus initiated a global pandemic, raising worldwide concerns. As mass screening decreased, testing waned, leading the WHO to declare the COVID-19 emergency over in May 2023. This study presents findings on the application of a serological Point of Care system for diagnosing, monitoring, and surveilling COVID-19 in atrisk individuals within a hospital setting. Methods: This cross-sectional retrospective study included serological immuno-fluorescent tests for immunoglobulin M (IgM) and immunoglobulin G (IgG) on samples from 742 individuals admitted to the Military Hospital (HIAOBO), encompassing healthcare workers and their families, vaccinated individuals, and persons recovered from COVID-19 between October 2021 and July 2022. Results: The study included 742 participants, predominantly female (52%), with an average age of 41.37 ± 14.62 years, and 55% were healthcare workers. The overall seroprevalence of IgM and IgG was 313 (42.18%) and 369 (49.73%), respectively. Among symptomatic cases, 54.05% tested positive for IgM and 69.73% for IgG. IgM and IgG were detected in 40.27% and 51.01% of HIV-infected patients, respectively, and in 37.50% and 40.20% of healthcare workers and their families. Conclusions: This study underscores the critical role of serological testing in understanding diverse immune responses. The findings offer valuable insights for developing tailored strategies for COVID-19 management.